2022
DOI: 10.37934/arfmts.96.1.179193
|View full text |Cite
|
Sign up to set email alerts
|

Using Micropolar Nanofluid under a Magnetic Field to Enhance Natural Convective Heat Transfer around a Spherical Body

Abstract: An analysis is discussed of the heat and mass transfer for micropolar nanofluid in presence of natural convection from a spherical body with magneto-hydrodynamic (MHD) effects. The constant wall temperature boundary condition is also studied. By employing proper similarity transformations, the governing equations are converted into a set of partial differential equations (PDEs) with the used boundary conditions, which can then be solved numerically via the efficient Keller-box implicit numerical finite differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…The numerical methodology was utilized to complete the numerical outcomes for the studied problem, where an above-considered system of partial differential Eq. (10) to Eq. ( 12) will be solved by the Keller box efficient method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical methodology was utilized to complete the numerical outcomes for the studied problem, where an above-considered system of partial differential Eq. (10) to Eq. ( 12) will be solved by the Keller box efficient method.…”
Section: Methodsmentioning
confidence: 99%
“…the convection boundary layer flow of laminar fluid flow which around the stretching sheet and vertical stretching sheet in the nanofluid has been studied by Khan and Pop [4], Makinde and Aziz [5], Kuznetsov and Nield [6], Kausar et al, [7]. Swalmeh et al, [8,9], Yaseen et al, [10], and Alwawi et al, [11] investigated the influences and impacts of micropolar nanofluid on the physical quantities around solid sphere and horizontal cylinder. Also, the heat transfer convection in Casson nanofluid considered by Alwawi et al, [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Alwawi et al [23][24][25][26][27] reported the effect of the magnetic field on the heat transmission rate of Casson nanofluid employing the Tiwari-Das model. See also [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53] According to a review of previous literature, 6,32,33,54 and based on the above potential and accomplishments, [17][18][19] the current gap has yet to be explored, despite the fact that this area has recently received tremendous attention from several scholars, as mentioned in previous studies. [17][18][19][45][46][47][48] Consequently, this work aims to numerically simulate the steady free convection of ethylene glycol as a micropolar fluid supported by copper nanoparticles or graphene oxide around a cylinder in the boundary layer region with an applied transverse magnetic field and a constant wall boundary temperature condition. On the other hand, the objective of this consideration is restricted to constructing the mathematical formulation for the studied problem subject to the boundary condition as dimensional governing equations and using suitable transformations to convert these equations to a system of partial differential equations (PDEs).…”
Section: Introductionmentioning
confidence: 99%
“…Alwawi et al 44 examined the promotion of MHD mixed convection of micropolar liquid past a cylindrical surface. Yaseen et al 45 studied the improvement of heat transfer through a magnetized micropolar liquid moving about a spherical surface. The previous references highlight studies involving the MHD effect.…”
Section: Introductionmentioning
confidence: 99%